Reversible Shifting of a Chemical Equilibrium by Light: The Case of Keto-Enol Tautomerism of a β-Ketoester - Lvov, Andrey G.; Yadykov, Anton V.; Lyssenko, Konstantin A.; Heinemann, Frank Wilhelm; Shirinian, Valerii Z.; Khusniyarov, Marat (Organic Letters, 2020)
Manipulating the equilibrium between a ketone and an enol by light opens up ample opportunities in material chemistry and photopharmacology. By incorporating β-ketoester into the ethene bridge of a photoactive diarylethene, we achieved reversible light-induced tautomerization to give thermally stable enol. In a pristine state, the tautomeric equilibrium is almost completely shifted toward the ketone. Photocyclization of diarylethene results in a new equilibrium containing a significant fraction of the enol tautomer.
CRIS-Team Scopus Importer:2020-02-04